2023
DOI: 10.3389/feart.2022.1037727
|View full text |Cite
|
Sign up to set email alerts
|

In-situ boron isotope and chemical composition of tourmaline in the Gyirong pegmatite, southern Tibet: Implications for petrogenesis and magma source

Abstract: Leucogranitic rocks, mainly including leucogranite-pegmatite systems, have been found to be widely distributed in the South Tibetan Himalaya, and they have received considerable interest because of their significance in crustal evolution and associated rare-metal mineralization. Although the nature and geodynamic setting of the Himalayan leucogranites have been well documented by numerous studies, the pegmatites spatially associated with these leucogranites are still poorly understood. Tourmaline is a ubiquito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 123 publications
(138 reference statements)
0
1
0
Order By: Relevance
“…Combining the local hydrological conditions, it is observed that groundwater in the aquifers exhibits low ow velocities and relatively long residence times, providing ample time for water-rock interactions. Additionally, considering prior research ndings, it is clear that ion exchange and mineral dissolution processes play a signi cant role in shaping hydrochemistry and groundwater types (Pei et al, 2023;Yang et al, 2023). To delve deeper into the rock control within water-rock interactions, employing end-member diagrams can elucidate the impact of various rock types on the ion composition of groundwater.…”
Section: Analysis Of Hydrochemical Characteristics Of Groundwatermentioning
confidence: 99%
“…Combining the local hydrological conditions, it is observed that groundwater in the aquifers exhibits low ow velocities and relatively long residence times, providing ample time for water-rock interactions. Additionally, considering prior research ndings, it is clear that ion exchange and mineral dissolution processes play a signi cant role in shaping hydrochemistry and groundwater types (Pei et al, 2023;Yang et al, 2023). To delve deeper into the rock control within water-rock interactions, employing end-member diagrams can elucidate the impact of various rock types on the ion composition of groundwater.…”
Section: Analysis Of Hydrochemical Characteristics Of Groundwatermentioning
confidence: 99%
“…Importantly, continental crust and most clastic metasediments have relatively low Ca contents and negative δ 11 B values (Rudnick and Gao, 2003;Trumbull and Slack, 2018), whereas marble and marine carbonate usually contain high Ca contents and positive δ 11 B values (Melezhik et al, 2005;Marschall and Jiang, 2011). Thus, the tourmalines derived from different sources show significantly different element and boron isotope compositions (Harlaux et al, 2020;Trumbull et al, 2020;Pei et al, 2023). This makes tourmaline an excellent messenger for tracing the origin of fluids (Marschall and Jiang, 2011;Harlaux et al, 2020;Trumbull et al, 2020;Chakraborty, 2021).…”
Section: Introductionmentioning
confidence: 99%